3y-2+3(2y+1)=-3(y+3)

Simple and best practice solution for 3y-2+3(2y+1)=-3(y+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-2+3(2y+1)=-3(y+3) equation:


Simplifying
3y + -2 + 3(2y + 1) = -3(y + 3)

Reorder the terms:
3y + -2 + 3(1 + 2y) = -3(y + 3)
3y + -2 + (1 * 3 + 2y * 3) = -3(y + 3)
3y + -2 + (3 + 6y) = -3(y + 3)

Reorder the terms:
-2 + 3 + 3y + 6y = -3(y + 3)

Combine like terms: -2 + 3 = 1
1 + 3y + 6y = -3(y + 3)

Combine like terms: 3y + 6y = 9y
1 + 9y = -3(y + 3)

Reorder the terms:
1 + 9y = -3(3 + y)
1 + 9y = (3 * -3 + y * -3)
1 + 9y = (-9 + -3y)

Solving
1 + 9y = -9 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
1 + 9y + 3y = -9 + -3y + 3y

Combine like terms: 9y + 3y = 12y
1 + 12y = -9 + -3y + 3y

Combine like terms: -3y + 3y = 0
1 + 12y = -9 + 0
1 + 12y = -9

Add '-1' to each side of the equation.
1 + -1 + 12y = -9 + -1

Combine like terms: 1 + -1 = 0
0 + 12y = -9 + -1
12y = -9 + -1

Combine like terms: -9 + -1 = -10
12y = -10

Divide each side by '12'.
y = -0.8333333333

Simplifying
y = -0.8333333333

See similar equations:

| 58=-x+171 | | y-(-9)=(-14/3)(x-(-9)) | | x/37+25=50 | | 7x+3=2x-17 | | 240=-w+30 | | (x+12)/(x-3)+1=(15)/(x-3) | | y-5=(-14/3)(x-(-6)) | | 77=(x/100)99 | | 1=2x-17 | | -5(v+1)=-4(2v-1)+9v | | 23=y/5+12 | | 2x-14=26 | | 15-4x=3 | | 4x+7y=209 | | 65*65-81*x*x=16*16*x*x | | 5y=-10/9 | | 5(y-5)-1=-2(-2y+6)-7y | | 14=-7/5u | | -2(2v-3)+7v=9+3(5v-2) | | 65*65-81*x*x=36*x*x | | -4/3w=24 | | 12-5/8 | | 3(-x+4)+6=-6x+3 | | 4/x-2=(-4/x+2)+(24/(x-2)(x+2)) | | 14m=400.40 | | 2n+7=5x | | 3v=3.75 | | 2(3x-5)=.5 | | 31.25=x/5 | | -2(x+2)=2x-1+5(2x+1) | | (7-x)(10-x)=(7)(10-1.5x) | | 6/10x=60 |

Equations solver categories